A living place: On the sociology of atmosphere in home museums. Issue 3 (3rd July 2017) - Dekel, Irit; Vinitzky-Seroussi, Vered
ABSTRACT: A darkened room, a cane, a hat on a bed: such items, former belongings of famous individuals, are presented in home museums in Israel and Germany. Such scenes are made to appear authentic through the mediation of objects and stories, which render them relatable to visitors but also strange and uncanny. Home museums are sites for the study of the sociology of atmosphere, which is constructed through what we term temporal multitude – linking stories, objects and the situatedness of visitors with historical narratives and their interpretation. Furthermore, such home museums create what we term a 'national memory atmosphere' in which specific national narratives are experienced as personal, thus stabilising relations between individuals and national memory. At the same time, they preserve those memories as multidimensional and open to revisiting. Here, we study the home museums of Adenauer, Brecht-Weigel, Einstein, Goethe, and Kollwitz in Germany and those of Agnon, Ben-Gurion, and Weizmann in Israel.